Case Study and Design Flare Package System for Waste Gas - A D Astuti, Yuliusman (International Journal of Advanced Science and Technology, 2020)
This study examines the important issue to determine flare header size extension fromoriginal location to new location of acid flare to prevent damage caused by overpressure.Gas flaring is a common practice used in many industrial processes such as refinery,petrochemical, and oil-gas industry to release flue gas. It is a must-have safetyrequirement which is installed to reduce excess pressure when the plant is shut down forannual repair, start up or emergency circumstance. With case study and design flarepackages system will get additional information because acid flare system has beendesigned based on the largest single risk with consideration of acid content. Methodsflare design studies will be using thermo-hydraulic model. The modelling will besimulated using AspenTechs FLARENET software with some scenario from existing acidflare system design basis for non-simultaneous relieving load and then new acid flare willreceive additional load from new unit. From the result of simulation, without changingthe size of tailpipe will cause the failure of PSV when the fire case occurred. So, start upwithout changing size of pipes is not recommended, change some tailpipe 3” into 4” toensure sufficient back pressure during fire case, for CV failure scenario to ensure backpressure sufficient during CV fail scenario, change type PSV from balance to pilot type